Net water uptake combined with neutrophil-to-lymphocyte ratio predictive value after successful recanalization in acute large vessel occlusion stroke - Jing, Xu; Liangxu, Xiang; Zhide, Li; Yue, Zhao; Yanghua, Tian (Frontiers in Neurology, 2025)
ObjectiveDespite successful recanalization after endovascular thrombectomy (EVT), some patients with acute large vessel occlusion stroke (ALVOS) have poor clinical outcomes. This study employed net water uptake (NWU) which was calculated based on the cranial CT on admission, to investigate the factors associated with the clinical outcomes of ALVOS patients with successful EVT recanalization.MethodsALVOS patients in anterior circulation with successful EVT recanalization were consecutively enrolled. NWU was measured in the middle cerebral artery territory based on the preoperative cranial CT, calculated by (1 − affected hemisphere density/ contralateral hemisphere density) × 100%. The neutrophil-to-lymphocyte ratio (NLR) was calculated from the blood routine test on admission. A poor 90-day outcome was defined as a modified Rankin Scale (mRS) > 2 points at 90-day after the index stroke.ResultsA total of 113 participants were enrolled. NLR (odds ratio [OR] = 1.31, 95% confidence interval [CI] = 1.09–1.58, p = 0.004) and NWU (OR = 1.48, 95% CI = 1.21–1.81, p < 0.001) were independently associated with poor 90-day outcomes. In the restricted cubic spline analysis, a significant nonlinear relationship was observed between NWU and an increased risk of 90-day poor functional outcome (p for nonlinear = 0.018). All participants were categorized into three grades based on 90-day mRS: complete independence (mRS 0–1 point), partial dependence (mRS 2–3 points), and complete dependence or mortality (mRS 4–6 points). In the multivariate ordinal logistic regression, both NLR (OR = 1.32, 95% CI = 1.12–1.56, p = 0.001) and NWU (OR = 1.29, 95% CI = 1.10–1.51, p = 0.002) were independently associated with the 90-day functional outcome grade. Receiver operating characteristic analysis demonstrated that the combination of NWU and NLR had the highest indicative value of poor outcome (area under the curve [AUC] = 0.800, 95% CI = 0.718–0.881, p < 0.001), followed by sole NWU (AUC = 0.764, 95% CI = 0.674–0.855, p < 0.001) and NLR (AUC = 0.662, 95% CI = 0.563–0.762, p = 0.003).ConclusionThe combination of NWU and NLR provides stronger indicative value of poor outcome compared to either marker alone.